Hedyotis corymbosa L. and Sterculia quadrifida R.Br Ethanolic Extract Enhances Cisplatin’s Cytotoxicity on T47D Breast Cancer Cells Through Cell Cycle Modulation - Rollando Rollando (Chemistry Department, The University of Brawijaya, 2018)
Chemotherapeutic agent such as cisplatin used as cancer cure with side effects and resistance. Ursolic acid is a compound found in Hedyotis corymbosa L., (HCoL) while 8-hydroxydehydrodunnione is found in Sterculia quadrifida R.Br (SQuR) which are proven to have cytotoxic effect to cancer cells. This research aims to review the effect of cisplatin, ethanolic extract of HCoL and SQuR to sensitivity increase on breast cancer cells, which will be confirmed through apoptosis induction and cell cycle modulation. The cytotoxic effect was tested using MTT assay on T47D cell by using IC50 parameter. The combination was tested by determining their combination index (CI) and cell viability. The combination effect in apoptosis induction and cell cycle modulation were observed using flow cytometry method. The cytotoxic test result of the combination shows CI value of below 1 at the concentration of HCoL ethanolic extract as much as 0,21 µg/mL, SQuR ethanolic extract as much as 0,45 µg/mL, and cisplatin as much as 2,5 µM. The combination of HCoL ethanolic extract, SQuR ethanolic extract, and cisplatin results in phase S cell accumulation (27,73%) on breast cancer cell T47D and was able to induct apoptosis. The result proves that ethanolic extract of HCoL and SQuR can developed as a co-chemotherapeutic agent to increase the effectivity of breast cancer treatment.